Eco-friendly mechanical performance of date palm Khestawi-type fiber-reinforced polypropylene composites - Abass, Raghad U.; Al-Sarraf, Mohammed Ausama; Bachtiar, Dandi; Mohd Ruzaimi, Mat Rejab (Walter de Gruyter GmbH, 2024)
Natural sources used in industry, such as environmental waste fibers for plants, waste paper, and others, can lessen waste-throwing problems and reduce environmental pollution to save lives on the earth’s crust. The natural composites of natural fiber-reinforced thermoplastic are undoubtedly to be sustainable and eco-friendly. Therefore, the current work was conducted to study the addition of natural fiber date palm Khestawi-type fiber (DPKF) with different loadings (5, 10, and 15%) into the polypropylene (PP) matrix to prepare DPKF/PP composites. The specimens were prepared by using the lamination method. In addition, the mechanical properties of these composite material specimens were studied by following ASTM, which included tensile, flexural, and impact tests. A scanning electron microscope (SEM) and X-ray diffraction (XRD) were employed to analyze the morphology and the structure crystallite studied of the DPKF/PP composites. The results show that the DPKF/PP composite with 15% fiber content recorded the best tensile strength, tensile modulus, and low tensile strain performance. Moreover, XRD and SEM analysis confirmed the mechanical properties and crystalline nature of the DPKF/PP composites. Finally, the values of the flexural and impact properties increased with increasing fiber loading.